Precocious secondary dentition: A case report - Kumar, Sunil; Juneja, Ruchi; Sharma, Shweta (Indian Journal of Child Health, 2019)
Chronology of human dentition possesses high variations and deviation from normal eruption timing. However, a significant deviation from routine observations might indicate a need to evaluate patient’s general health and development. This is because tooth eruption is influenced by multiple factors such as genetics, gender, socioeconomic status, craniofacial morphology, systemic diseases, and various syndromes. Presented here is an extremely rare case of early eruption of permanent canines and premolars in an 8-year-old male child. Although the number of such cases is very limited, the clinician should process adequate knowledge and should be vigilant to identify such cases.